Asian countries and the Arctic future - Lunde, Leiv; Yang, Jian, 1962 December 6-; Stensdal, Iselin (Singapore : World Scientific, 2016)
'Over the last few years Asian governments have taken a stronger approach to the Arctic, culminating with permanent-observer status to the Arctic Council for China, India, Japan, Singapore and South-Korea in May 2013. This groundbreaking book brings together the latest research in emerging Asian interests for the Arctic region, and the implications thereof this change has for the future. This book covers Arctic shipping, fisheries and mineral extraction. It analyzes key Asian countries' policies, positions and activities. The book also demonstrates that there are common aspects which attract Asian countries to the Arctic, such as a concern for climate change, but there are also important national differences. From the Arctic Council to UNCLOS, Arctic governance mechanisms are thoroughly presented and analyzed'--
Includes bibliographical references.
Keywords: Geopolitics -- Arctic regions; Asia -- Foreign relations -- Arctic regions; Arctic regions -- Foreign relations -- Asia